A method for preparing metal oxide electrode materials with UV light and heat assistance

Through the UV light thermal auxiliary preparation method, high -pressure mercury lamps are used for light thermal treatment, which solves the problem of high cost and low efficiency of traditional thermal treatment methods. performance.

CN116168956BActive Publication Date: 2025-01-28GUANGXI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310020008.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-01-28
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The prior art is difficult to apply on a large scale to the synthesis and processing of transition metal oxide materials, and traditional heat treatment methods have problems of high cost and low efficiency.

Method used

The UV light thermal auxiliary preparation method is adopted, and high -pressure mercury lamps are used as heating light sources to perform light thermal treatment of metal oxide electrode materials to achieve high -performance electrode materials.

Benefits of technology

This method not only reduces the cost of equipment, is suitable for large -scale production, but also improves electrochemical performance through the light and thermal effects induced by ultraviolet light, providing a better charge storage performance than traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116168956B_ABST
    Figure CN116168956B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing metal oxide electrode materials with UV photothermal assistance, the steps are: immersing a foam nickel substrate in dilute hydrochloric acid and ultrasonicating, then washing and drying; placing the dried foam nickel substrate in a reactor containing a reaction solution, drying after hydrothermal treatment, and obtaining a precursor of a CoMnO nanoarray; placing the precursor of the CoMnO nanoarray in the center of a quartz tube, and performing photothermal treatment under a protective gas condition with a low flow rate, to obtain a UV photothermal treated Co / Mn oxide material. The material preparation method of the present invention is simple, and can be obtained by only irradiating with UV light under a protective atmosphere without generating byproducts, and has the advantages of safe and green operation, short time, and is suitable for large-scale production. The method of the present invention can also be used to photothermally treat the precursor together with a nitrogen source or a sulfur source under a protective atmosphere for a period of time, so that nitrogen doping or sulfur doping can be simply and quickly performed, which can further improve the material performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitor materials, and in particular to a method for preparing metal oxide electrode materials with the assistance of UV light and heat. Background Art

[0002] At present, many research works have proved that carbon-based materials and pseudocapacitor materials such as graphene, RuO2, MnO2 and conductive polymers have very excellent capacitance properties as electrode materials for supercapacitors. Since the energy storage of such electrode materials is mainly carried out on the surface or near the surface of the active material, there are certain limitations in improving the energy density. In order to further improve the energy density of supercapacitors, it is necessary to introduce battery-type electrode materials that can achieve efficient redox reactions. Faraday redox reactions can penetrate into the bulk phase of the material, so battery-type electrode materials can usually provide higher capacity than carbon-based materials and pseudocapacitor materials. Studies have shown that hybrid supercapacitors with battery materials as positive electrodes and capacitor materials as negative electrodes can strike a good balance between power density and energy density, so battery-type metal oxide electrode materials show great prospects as supercapacitor electrodes.

[0003] Metal oxide electrode materials have great potential applications in the field of supercapacitors due to their ultra-high theoretical specific capacity. At present, transition metal oxide powder materials or film materials are generally obtained by heat treating their precursors in a resistance furnace at 300-1000°C. Compared with traditional heat treatment, microwave heating and laser heating methods are rarely used for transition metal oxide materials and are too expensive to be applied on a large scale.

[0004] In recent years, microwave heating and laser heating methods have been gradually applied to the synthesis and processing of functional materials with excellent electrochemical energy storage performance, such as graphene, carbon nanotubes, and graphene-supported catalysts. However, these methods are rarely used for transition metal oxide materials and are difficult to apply on a large scale.

[0005] Therefore, providing a method for UV photothermal assisted preparation of transition metal oxide electrode materials is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing transition metal oxide electrode materials with UV photothermal assistance. The present invention uses a high-pressure mercury lamp as a heating light source to heat treat the sample to obtain a high-performance electrode material. Compared with expensive laser heating and microwave heating equipment, the equipment required for this method is cheaper and can process samples on a large scale. Since the technology is mainly based on the photothermal effect induced by ultraviolet (UV) light emitted by a high-pressure mercury lamp, UV photothermal treatment of metal oxide materials has better electrochemical properties than traditional resistance furnace heating treatment.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a metal oxide electrode material by UV light-heat assistance comprises the following steps:

[0009] (1) immersing the nickel foam substrate in dilute hydrochloric acid and removing impurities and oxide layers on the surface by ultrasonic treatment, then fully washing the nickel foam substrate with water and ethanol respectively, and then placing the nickel foam substrate in a forced air drying oven for drying;

[0010] (2) taking ammonium fluoride, manganese nitrate, urea and cobalt nitrate and dissolving them in water to form a reaction solution, placing the dried nickel foam substrate into a reactor containing the reaction solution, performing hydrothermal treatment, and then washing and drying the reaction product to obtain a precursor of a CoMnO nanoarray;

[0011] (3) placing a precursor of the CoMnO nanoarray in the center of a quartz tube, placing a high-pressure mercury vapor lamp directly above the precursor of the CoMnO nanoarray, performing photothermal treatment under protective gas conditions, then keeping the temperature, and naturally cooling to room temperature to obtain a UV photothermal treated Co / Mn oxide material.

[0012] Furthermore, the size of the nickel foam substrate in step (1) is 2.5 cm×1 cm.

[0013] Furthermore, the concentration of dilute hydrochloric acid in step (1) is 0.1 mol / l

[0014] The ultrasonic power is 180W, and the ultrasonic time is 10min.

[0015] The beneficial effect of adopting the above further solution is that the above solution of the present invention can effectively remove pollutants such as oxides and grease on the surface of the nickel foam, which is conducive to the formation of the nano array.

[0016] Furthermore, in the reaction solution in step (2), the concentration of ammonium fluoride is 0.1 mmol / ml, the concentration of manganese nitrate is 0.067 mmol / ml, the concentration of urea is 0.2 mmol / ml, and the concentration of cobalt nitrate is 0.067 mmol / ml.

[0017] Furthermore, the hydrothermal reaction temperature in step (2) is 120° C., and the reaction time is 2-8 h;

[0018] The drying temperature is 60° C. and the drying time is 2-5 hours.

[0019] Furthermore, the power of the high-pressure mercury vapor lamp used in the photothermal treatment in step (3) is 2KW.

[0020] Furthermore, the photothermal treatment method in step (3) is: under light irradiation, the precursor of the CoMnO nanoarray is heated from room temperature to 350°C at a rate of 10°C / min and then kept warm for 2 to 5 hours.

[0021] The beneficial effect of adopting the above further scheme is that the above scheme can make full use of the ultraviolet light thermal effect to anneal the oxide precursor, and the obtained electrode material sample has excellent charge storage performance than the sample annealed by conventional tubular resistance.

[0022] Furthermore, the protective gas in step (3) is one of argon, nitrogen and helium.

[0023] The beneficial effect of adopting the above further solution is that the introduction of protective gas in the present invention can avoid oxidation of the foamed nickel on the sample substrate.

[0024] The beneficial effects of the present invention are as follows: the material preparation method of the present invention is simple, and can be obtained by only irradiating with UV light for a period of time under a protective atmosphere without generating byproducts, and has the advantages of safe and green operation, short time, and is suitable for large-scale production. The method of the present invention can also be used to perform photothermal treatment of the precursor together with a nitrogen source or a sulfur source under a protective atmosphere for a period of time, so that nitrogen doping or sulfur doping can be performed simply and quickly, which can further improve the material performance.

[0025] The method of the present invention regulates and optimizes the microstructure of nanosheets and nanowires through the photothermal synergistic effect induced by ultraviolet light, so that a more effective redox reaction occurs, which is more conducive to the adsorption of electrolyte ions and increases the energy storage capacity. It has advantages over the tubular furnace heat treatment method under the same conditions.

[0026] Compared with the traditional annealing treatment, the method of the present invention has better performance, simple preparation method, safe and green operation, short time and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XRD pattern of the UV-heat-treated Co / Mn oxide nanoarray prepared in Example 1 of the present invention;

[0028] Figure 2 This is a scanning electron microscope (SEM) image of the UV-heat-treated Co / Mn oxide nanoarray prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] Example 1 UV photothermal treatment of Co / Mn oxide precursor

[0032] 1) Immerse a 2.5 cm × 1 cm nickel foam substrate in dilute hydrochloric acid and remove surface impurities and oxide layers by ultrasonic treatment, then rinse the nickel foam substrate thoroughly with water and ethanol, respectively, and then place it in a forced air drying oven for drying;

[0033] 2) 3mmol of ammonium fluoride, 2mmol of manganese nitrate, 6mmol of urea, and 2mmol of cobalt nitrate were dissolved in 30mL of deionized water to prepare a reaction solution. A clean nickel foam substrate and the prepared reaction solution were placed in a reactor, and water was added to perform a hydrothermal reaction at 120°C for 2h. After the hydrothermal treatment, the reaction product was washed and dried at 60°C for 2h. The precursor of the CoMnO nanoarray was obtained;

[0034] 3) placing the CoMnO precursor obtained in step 2) in the center of a quartz tube, and placing a high-pressure mercury vapor lamp directly above the sample, and under the condition of a low flow rate of inert gas, heating the precursor of the CoMnO nanoarray from room temperature to 350° C. at a rate of 10° C. / min under light irradiation, then keeping the temperature for 3 hours, and naturally cooling to room temperature to obtain the UV photothermal treatment Co / Mn oxide material.

[0035] like Figure 1 The XRD pattern of CoMnO in this example is shown. After photothermal treatment, the diffraction peaks of CoMnO CoMn2O4 (PDF#77-0471) and mixed valence spinel (Co, Mn)(Co, Mn)2O4 (PDF#18-0408) are very consistent, indicating that Co / Mn oxide was successfully prepared by photothermal treatment.

[0036] like Figure 2 Shown is the SEM image of the Co / Mn oxide nanoarray treated with UV light thermal treatment in this example. It can be seen from the figure that the Co / Mn oxide nanoarray after UV light thermal treatment is evenly distributed on the surface of the nickel foam. These nanowires have rough edges and develop independently to form a three-dimensional porous structure.

[0037] Example 2 UV photothermal treatment of Co / Mn oxide nanoarrays

[0038] 1) Immerse a 2.5 cm × 1 cm nickel foam substrate in dilute hydrochloric acid and remove surface impurities and oxide layers by ultrasonic treatment, then rinse the nickel foam substrate thoroughly with water and ethanol, respectively, and then place it in a forced air drying oven for drying;

[0039] 2) 2 mmol manganese nitrate, 1 mmol cobalt nitrate, 3 mmol ammonium fluoride and 6 mmol urea were dissolved in 30 mL deionized water to prepare a reaction solution, and then the prepared solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene;

[0040] 3) Place clean nickel foam in the mixed solution and let it stand for 24 hours, then heat it at 120°C for 6 hours.

[0041] 4) After cooling the nickel foam loaded with the MnCo hydroxide precursor to room temperature, the foam was repeatedly washed with deionized water and dried at 60° C. for 24 h;

[0042] 5) The dried loaded MnCo hydroxide precursor is placed in a quartz tube, and the quartz tube is irradiated with a high-pressure mercury lamp for 2 hours in an argon environment for heat treatment, and the MnCo oxide nanoarray loaded on nickel foam is obtained after cooling to room temperature.

[0043] Example 3 UV photothermal treatment of Ni / Co oxide nanoarrays

[0044] 1) Immerse a 2.5 cm × 1 cm nickel foam substrate in dilute hydrochloric acid and remove surface impurities and oxide layers by ultrasonic treatment, then rinse the nickel foam substrate thoroughly with water and ethanol, respectively, and then place it in a forced air drying oven for drying;

[0045] 2) 2 mmol nickel nitrate, 1 mmol cobalt nitrate, 3 mmol ammonium fluoride and 6 mmol urea were dissolved in 30 mL deionized water to prepare a reaction solution, and then the prepared solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene;

[0046] 3) The clean nickel foam was placed in the mixed solution and allowed to stand for 24 hours, and then heated at 120° C. for 6 hours. After the nickel foam loaded with the NiCo hydroxide precursor was cooled to room temperature, it was repeatedly washed with deionized water and dried at 60° C. for 24 hours.

[0047] 4) The dried loaded NiCo hydroxide precursor is placed in a quartz tube, and the quartz tube is irradiated with a high-pressure mercury lamp for 2 hours in an argon environment for heat treatment, and after cooling to room temperature, a Ni / Co oxide nanoarray loaded with nickel foam is obtained.

[0048] Example 4 Photothermal treatment of nitrogen-doped Co / Mn oxide nanoarrays

[0049] 1) Immerse a 2.5 cm × 1 cm nickel foam substrate in dilute hydrochloric acid and remove surface impurities and oxide layers by ultrasonic treatment, then rinse the nickel foam substrate thoroughly with water and ethanol, respectively, and then place it in a forced air drying oven for drying;

[0050] 2) Prepare a solution with 3mmol ammonium fluoride, 2mmol manganese nitrate, 6mmol urea, 2mmol cobalt nitrate and 30mL deionized water, put the clean nickel foam and the prepared solution into a reactor, add water and heat at 120℃ for 2h. After hydrothermal treatment, the cleaned sample is dried at 60℃ for 2h. The precursor of CoMnO nanoarray is obtained;

[0051] 3) The CoMnO precursor obtained in step 2) and 2g of ammonium bicarbonate were placed in two transparent crucibles respectively, the two crucibles were placed in the center of the quartz tube, a high-pressure mercury lamp was placed directly above the sample, and a photothermal treatment was performed under low-flow argon conditions, the temperature was raised to 350°C at a rate of 10°C / min, and the temperature was kept for 3h. Finally, it was naturally cooled to room temperature and taken out to obtain a nitrogen-doped Co / Mn oxide nanoarray.

[0052] Example 5 Photothermal treatment of sulfur-doped Co / Mn oxide nanoarrays

[0053] 1) Immerse a 2.5 cm × 1 cm nickel foam substrate in dilute hydrochloric acid and remove surface impurities and oxide layers by ultrasonic treatment, then rinse the nickel foam substrate thoroughly with water and ethanol, respectively, and then place it in a forced air drying oven for drying;

[0054] 2) 3mmol of ammonium fluoride, 2mmol of manganese nitrate, 6mmol of urea, and 2mmol of cobalt nitrate were dissolved in 30mL of deionized water to prepare a reaction solution. The clean nickel foam and the prepared solution were placed in a reactor, and water was added for hydrothermal reaction at 120°C for 2h. After the hydrothermal treatment, the washed sample was dried at 60°C for 2h to obtain the precursor of the CoMnO nanoarray;

[0055] 3) The CoMnO precursor obtained in step 2) and 600 mg of sublimated sulfur are placed in two transparent crucibles respectively, the two crucibles are placed in the center of a quartz tube, a high-pressure mercury lamp is placed directly above the sample, and a photothermal treatment is performed under low-flow argon conditions, the temperature is increased to 350° C. at a rate of 10° C. / min, the temperature is kept for 3 h, and then naturally cooled to room temperature, and the sulfur-doped Co / Mn oxide nanoarray is obtained.

[0056] Comparative Example 1 Comparison between tube furnace annealing and photothermal treatment: XPS spectrum analysis, performance comparison

[0057] The scheme of tube furnace annealing is as follows:

[0058] 1) Immerse a 2.5 cm × 1 cm nickel foam substrate in dilute hydrochloric acid and remove surface impurities and oxide layers by ultrasonic treatment, then rinse the nickel foam substrate thoroughly with water and ethanol, respectively, and then place it in a forced air drying oven for drying;

[0059] 2) Prepare a solution with 3mmol ammonium fluoride, 2mmol manganese nitrate, 6mmol urea, 2mmol cobalt nitrate and 30mL deionized water, put the clean nickel foam and the prepared solution into a reactor, add water and heat at 120℃ for 2h. After hydrothermal treatment, the cleaned sample is dried at 60℃ for 2h. The precursor of CoMnO nanoarray is obtained;

[0060] 3) The obtained CoMnO precursor was placed in the middle of a quartz tube of a tubular furnace, and then annealed in an argon atmosphere, heated to 350°C at a rate of 5°C / min, kept warm for 120 minutes, and cooled to room temperature to obtain a nickel foam-loaded CoMnO nanoarray.

[0061] Compared with Example 1, the two main peaks of Co2p of CoMnO annealed in a tube furnace and CoMnO treated with UV light are 796.93eV, 780.83eV and 796.4eV, 780.52eV respectively. The binding energy of Co2p of CoMnO treated with UV light is shifted to a lower binding energy, which indicates that the barrier to extracting electrons from Co ions is very small and an effective redox reaction occurs in the Co species. The fitting of the spectrum shows that Co 2+ and Co 3+ At the same time, and by fitting Co 2+ and Co 3+ The XPS peak area of ​​Co in photothermal treated CoMnO 2+ With Co 3+ The ratio is 1.86, which is much smaller than that of tube furnace annealing (Co 2+ / Co 3+ =2.28), Co 3+ The increase of is beneficial to the adsorption of hydroxide, thereby improving the energy storage capacity.

[0062] Compared with Example 1, the UV photothermal treatment of CoMnO at 1 mA / cm 2 The mass specific capacitance is 1940 F / g, which is much larger than the 1376 F / g after tube furnace annealing, indicating that the UV light treatment successfully prepared the high-performance CoMnO electrode material.

[0063] Comparative Example 2: Comparison between pure light irradiation and light irradiation nitrogen doping: XPS spectrum analysis, performance comparison

[0064] Comparing Example 1 (pure illumination) with Example 5 (illumination nitrogen doping), compared with Example 1, Example 5 shows no obvious characteristic peak of nitrogen in the full spectrum after photothermal nitrogen doping. The N1s spectrum consists of two characteristic peaks: pyridinic nitrogen (398.5eV) and pyrrolic nitrogen (399.8eV). Pyridinic nitrogen accounts for 42% and pyrrolic nitrogen accounts for 58%. The Co2p binding energy after nitrogen doping shifts to a lower binding energy of 796.3eV (Co2p 1 / 2 ) and 780.27eV(Co2p 3 / 2 ), which is due to the charge transfer effect caused by the adsorption of foreign nitrogen atoms in the gap. 2+ and Co 3+ The XPS peak area of ​​Co after photothermal nitrogen doping 2+ With Co 3+ The ratio is 1.41, which is much smaller than that of pure light treatment (Co 2+ / Co 3+ =1.86). This demonstrates that nitrogen adsorption was successfully completed on the CoMnO nanowire arrays after photothermal treatment.

[0065] Compared with Example 1, Example 5 has a higher thermal conductivity at 1 mA / cm 2 The mass specific capacitance is 2534 F / g, which is much larger than the 1940 F / g of pure light treatment. This indicates that this method successfully performs nitrogen doping during photothermal treatment of precursors, thereby improving the electrochemical properties of mixed metal oxide materials.

[0066] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing metal oxide electrode materials by UV photothermal assistance, characterized in that: The following steps are involved: (1) immersing the nickel foam substrate in 0.1 M dilute hydrochloric acid and removing impurities and oxide layers on the surface by ultrasonic treatment, then washing the nickel foam substrate with water and ethanol respectively, and then drying it in a forced air drying oven at 60° C.; (2) taking ammonium fluoride, manganese nitrate, urea and cobalt nitrate and dissolving them in water to form a reaction solution, placing the dried nickel foam substrate into a reactor containing the reaction solution, performing hydrothermal treatment, and then washing and drying the reaction product to obtain a precursor of the CoMnO nanoarray; the concentration of ammonium fluoride in the reaction solution is 0.1 mmol / ml, the concentration of manganese nitrate is 0.067 mmol / ml, the concentration of urea is 0.2 mmol / ml, and the concentration of cobalt nitrate is 0.067 mmol / ml; (3) The precursor of the CoMnO nanoarray and ammonium bicarbonate or sublimated sulfur are placed in the center of a quartz tube, and a high-pressure mercury vapor lamp is placed directly above the precursor of the CoMnO nanoarray. The power of the high-pressure mercury vapor lamp is 2 kW. Under protective gas conditions, the precursor of the CoMnO nanoarray is heated from room temperature to 350°C at a rate of 10°C / min under light irradiation and then kept warm for 2-5 hours to complete the photothermal treatment. Subsequently, the temperature is kept and naturally cooled to room temperature to obtain a UV photothermal treated Co / Mn oxide material.

2. The method for preparing metal oxide electrode materials by UV photothermal assisted method according to claim 1, characterized in that: The size of the nickel foam substrate in step (1) is 2.5 cm×1 cm.

3. The method for preparing metal oxide electrode materials by UV photothermal assisted method according to claim 1, characterized in that: The concentration of dilute hydrochloric acid in step (1) is 0.1M The ultrasonic power is 180W, and the ultrasonic time is 10min.

4. The method for preparing metal oxide electrode materials by UV light-heat-assisted method according to claim 1, characterized in that: The hydrothermal reaction temperature in step (2) is 120° C. and the reaction time is 2-8 h; The drying temperature is 60° C. and the drying time is 2-5 hours.

5. The method for preparing metal oxide electrode materials by UV photothermal assisted method according to claim 1, characterized in that: The protective gas in step (3) is one of argon, nitrogen and helium.

Citation Information

Patent Citations

  • Manganese cobalt oxide porous nanometer sheet / foam nickel compound electrode material preparation method

    CN105244191A

  • Low-temperature liquid phase method for preparing high-dielectric yttrium oxide thin film

    CN106298455A